Hybridised materialisms: The 'twists and turns' of materialities in feminist theory. (August 2019) - Zouggari, Najate
This article examines the conceptualisation of materialities in feminist theory through two paradigmatic examples: (French) materialist feminism and new materialisms. What can be interpreted as an opposition between different paradigms can also be disrupted as long as we define what matters as a relation or a process rather than a substance or a lost paradise to which we should return. New materialisms indeed help to investigate aspects such as corporeality, human/non-human interaction and textures, but the role of feminist materialism is invaluable in highlighting the social structures of power relations; more than ever, it makes a decisive contribution to the understanding of domination, such as the social relations and hierarchies implied in femosecularism conceptualised in this article. Ultimately, the tool of hybridised materialisms aims to articulate the theoretical perspective of materialist feminism with that of the new materialisms – in order to avoid the binarism between materiality and culture.